3 - La chefferie traditionnelle au Cameroun: ambiguïtés juridiques et dérives politiques: 10.4314/ad.v25i3.22103 - Mback, Charles Nach (Africa Development, 2000)
It seems that traditional chiefdoms in Africa have never recovered from the trauma caused by their contact with the first European colonisers. The post- colonial state has perpetuated the emasculation of traditional authorities appointed by the colonisers. From devaluing status of servants of colonisation, traditional chiefs were enlisted in single party systems. In both cases, they have lost an important part of their creditworthiness among populations. The latter, however, remain sometimes devoted in spite of all. But these traditional chiefs have never had the opportunity to get back their original autonomy, neither legally, nor politically. As human communities, chiefdoms are sometimes undervalued within the local communities, sometimes equated with existing administrative districts. The new local administration system resulting from the new constitution does not bring any decisive and qualitative changes on these issues, whereas very few possibilities remain open for both constitutional and regulatory standpoints.